The Wagner Group - Habib Badawi; Mohamad Daabul (Arab Journal for Security Studies)
This study includes the mysterious World Wagner, a private military company, which is said to be related to Russian interests around the world. The awthors also explore its emerging origins and implications, and seek to provide a comprehensive analysis of this secret organization, highlighting its origins, its key figures, its global record, and its countless challenges to security and diplomacy. The methodology of this study includes collecting data from various primary and secondary sources, including official documents and academic literature. And analyze the data to identify major themes and patterns. The study conducts a comparative analysis of other private military companies, examines the legal framework, analyzes media coverage, and focuses on ethical considerations. In conclusion, the study presents a set of recommendations, including: Strengthen international cooperation, create strong legal frameworks, and implement targeted sanctions to regulate private military companies such as: Wagner. Future research should explore case studies and socio-economic impacts.